The impact of suburbanization on social differentiation in Hungary: a case study of the Miskolc agglomeration - Kristóf, Andrea (Geographica Pannonica, 2018)
The aim of this paper is to present how the socio-economic processes of the past few years have affected Miskolc (presently the fourth largest city in Hungary) and the nearby suburban settlements with special regard to changes in population, educational attainment, motivations for suburbanization and satisfaction with suburban living conditions. In addition to the analysis of related statistics, the paper reports the results of a residential questionnaire survey, conducted in the suburbs of the Miskolc agglomeration. The paper argues that the suburbanizing process has resulted in the social restructuring of the suburban settlements of the Miskolc agglomeration. Results prove that suburbanization has played an important role in improving educational attainment figures in suburbs, since two-fifths of people involved in suburbanization (according to the questionnaire survey) completed tertiary education, which is higher than the average of Miskolc and the agglomeration. It has been shown that better living conditions (less polluted, less crowded residential areas) have been one of the most important factors for suburbanization in the Miskolc agglomeration, since it has been revealed that the majority of people involved in suburbanization previously lived in one of the crowded housing estates in Miskolc, in the immediate neighborhood of heavily polluting industrial plants. Empirical results also show that suburban residents are least satisfied with job opportunities and their financial position, while they are most satisfied with healthcare services, natural environment and public transport. Finally, it has been found that suburban settlements only provide basic services (e.g. family doctor), thus local residents generally heavily rely on the higher-level services (e.g. banking) of Miskolc.